EVALUASI KETAHANAN MUTAN PADI BERAS HITAM TABAH HASIL IRADIASI SINAR GAMMA Co-60 TERHADAP PENYAKIT - Luthfiyyah, Siti Raihany; Rianto, Fadjar; Syahputra, Edy (Fakultas Pertanian Universitas Tanjungpura, 2020)
The production of black rice has decreased due to disease attacks. One way to improve rice resistance to disease is through the induction of mutations with gamma ray radiation. The purpose of this study is to evaluate the resistance of black rice induced by Co-60 by 0 Gy, 200 Gy and 300 Gy against disease. The research was conducted on BBI's land in Sungai Kakap Village, Kubu Raya Regency during one planting season, from October 2017 to April 2018. This research used a descriptive research method. Each treatment was observed as many as 50 rice plants, so that the total sample of observation is 150 plants. Observations were made 3 times, during vegetative, maximum vegetative, and generative periods. Disease identification is done in two ways which are macroscopic and microscopic. Assessment of the severity of the disease is guided by the guidebook. The results of the study found 4 diseases that attack black rice mutant plants, namely narrow brown spots, leaf and collar blast disease, fusarium disease, and midrib blight. Narrow brown spot disease, rice irradiated by 200 Gy is the most resistant with medium - rather resistant category. Leaf blast disease, rice that is not irradiated is most resistant with medium - rather resistant category. Panicle blast disease, rice irradiated by 200 Gy is most resistant with medium - resistant category. Keywords: Black rice, Cobalt-60 induction, disease scoring